Inflammatory Biomarkers in Coronary Artery Ectasia: A Systematic Review and Meta-Analysis - Dimitrios A. Vrachatis; Konstantinos A. Papathanasiou; Dimitrios Kazantzis; Jorge Sanz-Sánchez; Sotiria G. Giotaki; Konstantinos Raisakis; Andreas Kaoukis; Charalampos Kossyvakis; Gerasimos Deftereos; Bernhard Reimers; Dimitrios Avramides; Gerasimos Siasos; et al. (Diagnostics, 2022)
Isolated coronary artery ectasia (CAE) is a relatively rare clinical entity, the pathogenesis of which is poorly understood. More and more evidence is accumulating to suggest a critical inflammatory component. We aimed to elucidate any association between neutrophil to lymphocyte ratio and coronary artery ectasia. A systematic MEDLINE database, ClinicalTrials.gov, medRxiv, Scopus and Cochrane Library search was conducted: 50 studies were deemed relevant, reporting on difference in NLR levels between CAE patients and controls (primary endpoint) and/or on high-sensitive CRP, IL-6, TNF-a and RDW levels (secondary endpoint), and were included in our final analysis. (PROSPERO registration number: CRD42021224195). All inflammatory biomarkers under investigation were found higher in coronary artery ectasia patients as compared to healthy controls (NLR; SMD = 0.73; 95% CI: 0.27–1.20, hs-CRP; SMD = 0.96; 95% CI: 0.64–1.28, IL-6; SMD = 2.68; 95% CI: 0.95–4.41, TNF-a; SMD = 0.50; 95% CI: 0.24–0.75, RDW; SMD = 0.56; 95% CI: 0.26–0.87). The main limitations inherent in this analysis are small case-control studies of moderate quality and high statistical heterogeneity. Our findings underscore that inflammatory dysregulation is implicated in coronary artery ectasia and merits further investigation.